The Role of Maritime Intelligence Agency in Fostering the Basics of National Maritime Resilience in Indonesia - Kusumaningrum , Adi; Moeljadi, Moeljadi; P., Widyanto Pudyo; Wijaya, Windu Wahyu (Future Science, 2024)
Excellent relations between the coordinator Ministry for maritime affairs and Investment as users with all stakeholders in the maritime domain as a collector of maritime intelligence data must be established so that users or decision-makers could make the right decisions promptly. Qualitative research is then conducted to find out what hindrances can impede the smooth supply of maritime intelligence data from collector to user and to look into requirements to produce good quality intelligence data for users. The research's data are obtained through library research and then analyzed through the data collection phase, data condensation phase, and data display phase. Finally, it ended by concluding that it is timely for the Indonesian government to create a maritime intelligence agency by grouping intelligence personnel from each maritime stakeholder, which performs maritime intelligence data gathering separately. The next new agency would serve as the only government body to supply maritime intelligence data for users. By doing so, sectoral ego and other hindrances, which often impede unity in serving the country, would be abolished. Additionally, maritime intelligence data sent to users must reflect the truth on the ground from several reliable intelligence sources.